2015
DOI: 10.1002/2327-6924.12243
|View full text |Cite
|
Sign up to set email alerts
|

Infant and child deaths: Parent concerns about subsequent pregnancies

Abstract: Purpose Examine parents’ concerns about subsequent pregnancies after experiencing an infant or child death (newborn to 18 years). Data sources Thirty‐nine semistructured parent (white, black, Hispanic) interviews 7 and 13 months post infant/child death conducted in English and/or Spanish, audio‐recorded, transcribed, and content analyzed. Mothers’ mean age was 31.8 years, fathers’ was 39 years; 11 parents were white, 16 black, and 12 Hispanic. Conclusions Themes common at 7 and 13 months: wanting more children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…The data describe a range of reactions to loss, and highlight the personal and individual nature of timing a subsequent pregnancy. This is consistent with other studies 18 62–64 64–68. Our findings suggest that parents may feel increased isolation after fetal or perinatal death, due to the taboo nature of the topic 18 69 70.…”
Section: Discussionsupporting
confidence: 92%
“…The data describe a range of reactions to loss, and highlight the personal and individual nature of timing a subsequent pregnancy. This is consistent with other studies 18 62–64 64–68. Our findings suggest that parents may feel increased isolation after fetal or perinatal death, due to the taboo nature of the topic 18 69 70.…”
Section: Discussionsupporting
confidence: 92%
“…Although many parents were prepared to move on and proceed with a subsequent pregnancy, they were adamant that doing so was not a means to forget or replace their previous child. These findings were similarly reported in Campbell‐Jackson et al (2014) and Brooten et al (2015) who found that although the parents' emphasis was on the next child, it was still important for them to maintain a ‘relationship’ and keep the memory of their previous child alive for themselves, their families and communities. Healthcare administrations should ensure that healthcare professionals receive adequate and necessary training so that they can be more wary and sensitive to such needs and allow open conversations where parents can discuss previous losses.…”
Section: Discussionsupporting
confidence: 80%
“…More scarce are the studies that analyze these consequences in pregnancies that take place after a gestational loss, with similar results (Al-Maharma, Abujaradeh, Mahmoud, & Jarrad, 2016;Brooten et al, 2015;Chojenta et al, 2014;Üstündağ-Budak, Larkin, Harris, & Blissett, 2015).…”
Section: Discussionmentioning
confidence: 96%